PENINGKATAN KREATIVITAS SISWA KELAS 4 SDN 9 AMPENAN MELALUI PENERAPAN MODEL PROJECT BASED LEARNING PEMBUATAN CELENGAN - Anggriani, Ririn; Nabila, Riska; Saputra, Roy; Aynun, Rizqa; Hartina, Siti; Rahmaniah, Rima; Mulianto, Agus (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to enhance the creativity of fourth-grade students at SDN 9 Ampenan through the implementation of the Project Based Learning (PjBL) model in the subject of Visual Arts, focusing on the creation of simple piggy banks. The method used is Classroom Action Research (CAR), conducted in two cycles involving 30 students (21 males and 9 females). Each cycle consists of planning, implementation, observation, and reflection stages. Data collection techniques include observation, questionnaires, and interviews. Data were analyzed descriptively and comparatively. The research results show a significant increase in students' creativity from Cycle I to Cycle II. In Cycle I, the average creativity score of students was 70% (fairly creative), while in Cycle II, it increased to 85% (creative). Students demonstrated high enthusiasm and creativity development through the project of making piggy banks from recycled materials. Based on these findings, the Project Based Learning model proves effective in fostering student creativity within a relevant and meaningful learning context.